On the dichotomic and trichotomic problems for dynamic programming process with finite number stages - Bistrickas, V. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:B. Б. Бистрицкас. К вопросу дихотомической и трихотомической задач динамического программирования для процесса с конечным числом шаговV. Bistrickas. Dinaminio programavimo proceso su baigtiniu žingsnių skaičiumi dichotominio ir trichotominio uždavinio klausimu